(untitled) (Scientific journal of the Fergana State University, 2025)
This study focuses on some scientific works such as treatment of various wastewaters and effluents, ion exchange, gas separation, metal separation, etc., and provides a general overview of the latest scientific developments in the field of application and modification of membranes made of ion exchange sorbents and granular sorbents. Also, the production of anion exchangers based on polyethylenepolyamine and their alternative conditions were considered. Methods for modifying polyethylenepolyamine under heterogeneous conditions using modifiers containing amino and carboxyl groups were also described. Various ion exchange sorbents and membranes based on polyethylenepolyamine, methods for modifying polyethylenepolyamine, and the use of the obtained ion exchange sorbents and membranes are considered. Comparison of the sorption properties of ion exchange sorbents and sorbents based on polyethylenepolyamine used in industry was carried out.